Efektivitas SIPKD, Gaya Kepemimpinan, dan Lingkungan Kerja Pada Kinerja Karyawan Dinas Pariwisata Provinsi Bali - Brawijaya, I Gusti Agung; Yenni Latrini, Made (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p18, 2020)
Employee Performance plays an important role in the success of an organization. An organization expects employees to complete tasks in a timely, accurate, and reliable manner. One form of government in improving the performance of its employees is the application of SIPKD. This research was conducted at the Bali Provincial Tourism Office. The purpose of this research is to find out how much effectiveness SIPKD, leadership style, and work environment have on employee performance. The sample selection method in this study uses the saturated sample (census) technique. The number of samples in this study were 40 people. The results of this study indicate that the effectiveness of SIPKD has no significant effect on employee performance. While the leadership style and work environment have a positive and significant influence on the performance of the employees of the Bali Provincial Tourism Office. Keywords: Effectiveness of SIPKD; Leadership Style; Work Environment.